KUALITAS PENGALAMAN DALAM MEMODERASI KUALITAS PRODUK DAN HARGA TERHADAP REVISIT (Studi Kasus Pada Konsumen Shampo Merk Clear) - Mursida Kusuma Wardani; Catia Laila Ferdiansyah; Dede Indri; Putri Naurah Nazhifah; Surya Bintarti (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Trend hair style is a phenomenon that always appears with the times. Clear was launched in Indonesia in 1975 and is produced by PT Unilever Indonesia Tbk. Based on the Top Brand Index data, it can be seen that clear is in 2nd place. This brand from Unilever pioneered shampoos specifically for women and specifically for men which were created in 1997 because they wanted to provide a solution to dandruff. The aim of the study was to examine the effect of experience quality on revisit moderated by product quality and price on clear shampoo. The research was conducted within the boundaries of the community area of Bekasi district. The number of samples obtained by 74 respondents. This study shows that the quality of experience has an effect on repurchase intention, the quality of experience which is moderated by product quality has no effect on repurchase intention while the quality of experience which is moderated by price can have a significant effect on repurchase intention.